Las regletas de Cuisenaire: Un recurso subestimado en la enseñanza de las fracciones - Ortega Villamagua, Viviana Nayely (2024)
This research paper called “Cuisenaire's Rods: An underestimated resource in the teaching of fractions”, set a general objective, to contribute to the learning of fractions using Cuisenaire's Rods as a didactic resource with students in the sixth year of General Basic Education at "José Ángel Palacio" School. In the same way, the specific objectives were: to diagnose the students fraction learning level, to propose a didactic guide with activities using Cuisenaire's rods as a resource in the teaching of fractions, and, to evaluate the effectiveness of the didactic guide in the learning and understanding of fractions. The present investigation was developed through a qualitative-quantitative approach, descriptive type; non-experimental transversal design. The scientific, analytical, descriptive and statistical method were used and also some techniques like the interview and diagnostic evaluation, the instruments applied were the question guide and the pre- and post-evaluation questionnaire; the population consisted of 1 teacher and 14 students who were selected by means of a non-probabilistic sampling; the results obtained in the post-test were satisfactory, due to the implementation of the educational proposal "Mathematics with colored rods" proved to be a significant improvement in the students' performance, especially in the understanding of fractions, these results highlight the effectiveness of practical and visual approaches for students who presented learning problems in relation to fractions. Thus, the implementation of pedagogical strategies that integrate Cuisenaire's colored rods allows the teacher to offer more dynamic and meaningful learning experiences by allowing students to physically manipulate the rods, promoting a deeper understanding of this mathematical skill.